Early-age deformation of cement emulsified asphalt mortar with aluminum powder and expansive agent. (10th November 2020) - Yuan, Qiang; Zuo, Shenghao; Deng, Dehua
Highlights: The early-age deformation behaviors of CA mortar with AP and/or UEA were studied. Deformation results from the graduated flask method and the buoyancy method were compared. Four deformation stages of CA mortar were found and the underlying mechanisms were discussed. Abstract: Early-age deformation of cement emulsified asphalt mortar (CA mortar) is a key parameter for its application in the CRTS I and CRTS II slab ballastless tracks of China. In this paper, the buoyancy method was used to measure the early-age deformation behaviors of CA mortars with aluminum powder (AP) and/or U-type expansive agent (UEA). The results indicate that the buoyancy method accurately and stably reflects the early-age deformation of CA mortar. The deformations of CA mortars with AP and/or UEA are composed of four stages: slight shrinkage stage, fast expansion stage, gradual shrinkage stage, and stable stage. Further analyses of relative expansions of samples reveal that different mechanisms of AP and UEA take effect at the gradual shrinkage stage of CA mortar deformation. Thermal effect induced by internal heat accumulation increases the air pressure in voids entrained by AP in CA mortar, thereby increasing the peak deformation values. Then the deformation tends to decrease with heat dissipation at the gradual shrinkage stage. Similar shrinkage stage is also observed in field tests. The buoyancy method can reflect the entire early-age deformation process of CA mortar with AP. This method is more suitable for engineering applications than the graduated flask method which is standardized in the specifications of China.